A simple but efficient tumor-targeted nanoparticle delivery system constructed by oleic acid. (31st December 2022) - Fu, Jingxin; Wang, Yian; Li, Haowen; Lu, Likang; Han, Meihua; Guo, Yifei; Wang, Xiangtao
Abstract: Oleic acid (OA) is a kind of monounsaturated omega-3 fatty acid that abounds in plants and animals which can induce apoptosis and has broad-spectrum inhibitory activity against a variety of tumor cell lines. However, OA is quite insoluble and thus inconvenient to be efficiently delivered in vivo. In this work, OA was fabricated into nanoparticles to generate OA elastic nanoparticles (OA-ENPs) with a particle size of 185.6 nm and good stability in various physiological media. OA-ENPs alone achieved a high tumor inhibition rate of 60.3% without significant side effect. More surprisingly, the resultant OA-ENPs displayed dose-dependent tumor targetability. Low dose of OA-ENPs (10 mg/kg) mainly distributed in the liver after intravenous injection, while high dose of OA-ENPs mainly distributed in tumor. At the high dose of 90 mg/kg, OA-ENPs accumulation in tumor reached nearly twice as that in the liver. Here we provide a simple but effective way to achieve excellent tumor targetability without the need of any surface modification of nanoparticles.